PERANAN KODE ETIK PROFESI NOTARIS DALAM MENJUNJUNG TINGGI JABATAN NOTARIS DI KOTA BANJARMASIN - , BAMBANG SUSANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims at exploring the implementation of the Code of Professional Ethics and Compliance Notary After the Code Enforcement in Banjarmasin. Results of this study showed that there are adherence and violation in the implementation of the Code Notary in Banjarmasin . Code of Ethics adhered are i This research was an empirical legal research which involved primary data obtained from field research in the form of interviews with many informants and respondents who were relevant to the research problems. It also involves materials relating to the research topic which served as secondary data in law field. To analyze data, a qualitative descriptive study was conducted. mprove the knowledge on Legal Studies, perform the daily duties in one office which becomes Offices the only office for the Notary to implement daily tasks, lace 1 (one) sign in front of his / her office environment, Place one (1) signpost in front of the office with the size appropriate to the requirement of Notary Code, present and join each meeting held by the organization of Indonesian Notaries Association (INI). Code of Ethics violated are the size of nameplate that does not comply with the provisions of Code of Notaries